Breathing lessons - Tyler, Anne (new york the berkley publishing group, 1998)
Maggie with her scatterbrained attempts to make everything right for everyone... and Ira , infinitely patient, who's addicted to solitaire and who whistles out popular tunes, the only barometer of his moods.they've learned all there is to know about each other - two ordinary lives in a comfortably routine marrige. but on the road to a friend's funeral, they make some unexpected detours and discover how extraordinary their ordinary lives really are
American corner
winner of the pulitzer prize
11
Keywords: English fiction; English novels; Novels